2021
DOI: 10.1016/j.ssmph.2021.100916
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effect heterogeneity in the head start impact study: A systematic review of study characteristics and findings

Abstract: There have been consistent efforts to assess treatment effect heterogeneity (TEH) of Head Start using the data from the Head Start Impact Study (HSIS), a randomized controlled trial of a federally funded child development program for a nationally representative sample of low-income parents and their 3- and 4-year-old children in the United States. Including 28 studies on TEH of Head Start, this review found that multiple high-risk subgroups (e.g., children with lower cognitive abilities, Spanish-speaking dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…They further examined for which subgroups of children Head Start was effective and found that the program in general had compensatory effects, or greater benefits for those with greater needs. 11 Head Start benefitted several subgroups with more disadvantages, such as children with Spanish as a primary language, 12 , 13 those who had lower cognitive skills at baseline, 12 , 13 and those with home-based or non-parental care. 14 16 However, further examination of HTE in Head Start is needed because findings on the treatment effects were mixed for many other disadvantaged subgroups, such as children with low parental education level, 17 , 18 special needs, 19 single parents, 20 or caregivers with depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They further examined for which subgroups of children Head Start was effective and found that the program in general had compensatory effects, or greater benefits for those with greater needs. 11 Head Start benefitted several subgroups with more disadvantages, such as children with Spanish as a primary language, 12 , 13 those who had lower cognitive skills at baseline, 12 , 13 and those with home-based or non-parental care. 14 16 However, further examination of HTE in Head Start is needed because findings on the treatment effects were mixed for many other disadvantaged subgroups, such as children with low parental education level, 17 , 18 special needs, 19 single parents, 20 or caregivers with depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…A common methodological approach of the previous studies on HTE was a subgroup analysis which restricts the analysis to a subgroup or tests for statistical interactions between the treatment and covariates of interest (e.g., gender, race/ethnicity). 11 However, such an approach has been shown to be insufficient in capturing HTE because it still relies on ATE. 22 While one can test whether ATE estimates are heterogeneous across selected subgroups, heterogeneity around those estimates remains masked.…”
Section: Introductionmentioning
confidence: 99%
“…Since the conclusion of the HSIS, studies have examined the potential heterogeneity of treatment effects of the Head Start, and there have been reviews summarizing the findings (S. Y. Lee et al, 2021 ; Morris et al, 2018 ). Most attempts focused on subgroup or interaction analyses, investigating children's individual or environmental characteristics as sources of effect heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of follow-up studies using the same data have revealed substantial variation in the effects of Head Start, with one study reporting a pattern of the Head Start having larger positive effects for systematically more excluded subgroups of children such as Hispanics, those with low maternal education level, and those who had low cognitive measures at baseline (S. Y. Lee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation